Clinical Significance of the Transcription Factor SOX11, Cell-Cell Adhesion Protein E-cadherin and Zinc Finger Protein BCL11A in the Diagnosis of Breast Cancer - Salma Salama; Nadia Hamdy; Reham El-Shimy; Hala El-Mesallamy (Ain Shams University, 2021)
Transcription factors (TFs) as SRY-Box transcription factor 11 (SOX11) and B-cell lymphoma/leukemia 11A (BCL11A) role in breast cancer (BC) as well as their effect on epithelial cadherin (E-cadherin) membrane protein which is a metastasis suppressor is a question that must be addressed. Among the thirty-nine BC patients were invasive ductal carcinoma (IDC), twenty females with benign fibroadenomas and/or fibrocystic changes and nineteen healthy control. We quantified SOX11, E-cadherin and BCL11A serum levels in Egyptian women with BC and determined their cut-off values. The correlation between SOX11, E-cadherin and BCL11A sera levels and cancer antigen (CA15.3) as well as carcino-embryonic antigen (CEA) were assessed and quantified by ELISA. Finally, we explored the association between SOX11, E-cadherin levels, and BCL11A as potential markers according to histo- and clinicopathological characteristics and hormones receptors. Significant increase in E-cadherin serum levels in the cancerous than the non-cancerous group (p  0.05). A significant decrease in SOX11 and BCL11A serum levels (p < 0.05) was detected in the non-cancerous group than the cancerous group. In addition, a decrease in SOX11 levels was observed in the later stage of BC cases, while earlier stage BC cases were associated with an increase in SOX11. In addition to the significant positive correlation (p < 0.05) between SOX11 and BCL11A proteins in blood suggesting a common inter-regulatory pathway. SOX11 has an excellent area under the curve (AUC) either solely or combined with CA15.3. Earlier stages in BC were associated with an increase in SOX11 serum levels (p < 0.05).